Statin Intolerance in a Patient with Gilberts Syndrome and Hypercholesterolemia - Jialal, I.; Siegel, D. (Experimental and Clinical Endocrinology & Diabetes Reports, 2016)
Background: Statin intolerance especially myalgias can be a serious problem. Whilst it is well know that drugs that compete for Cytochrome 450 system can result in myalgias there is sparse data on the role of glucuronidation of statins contributing to statin intolerance We report on a 60 year old male with Hypercholesterolemia (HC) who was referred for management of his HC since he had statin intolerance manifesting as myalgias and was shown to have Gilbert’s Syndrome.Case Report: Investigation of this patient revealed he had Familial Combined Hyperlipidemia with a LDL-cholesterol of 189 mg/dl. He was also diagnosed with Gilbert’s Syndrome since he had elevated unconjugated bilirubin with no evidence of liver disease or hemolysis. The combination of Niacin, Cholestyramine and ezetimibe resulted in a successful decrease in his LDL-cholesterol to 114 mg/dl.Discussion: We believe that his Gilberts Syndrome resulted in an impairment in glucuronidation of statin drugs resulting in an increase in free drug levels and myalgias. We caution that clinicians should consider this possibility when confronted with a patient with both isolated elevations of unconjugated bilirubin and increase LDL-cholesterol levels before commencing statin therapy.
Keywords: LDL; cardiovascular risk management; coronary artery disease